IMPLEMENTATION OF THE TILAWATI METHOD IN LEARNING TAHFIDZ OF THE QURAN TO IMPROVE THE QUALITY OF CHILDREN'S READING - Samsul Fajeri; Husin; Farida Hendriyani; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Memorizing the Koran is one form of our efforts to get closer to Allah SWT through His words. The tilawati method is a book of teaching and learning methods to read the Koran with a balanced classical-read-listen approach. The implementation of the Tilawati Method in learning the tahfidz of the Koran to improve the quality of reading the Koran is a process of reading verses that must be memorized perfectly and becomes a good quality reading. This study aims to find out how the tilawati method becomes a method that focuses on how to read the Koran easily and pleasantly, by using this tilawati method students can find out how to recite the Koran so that reading the Koran becomes quality reading at TPA Hidayatul Science Unit 332 Village Paliat. The methodology used in this study was carried out by field observation which is a descriptive qualitative research. Based on the results of this study, the Implementation of the Tilawati Method in Tahfidz Koran at TPA Hidayatul Ilmi Unit 332 in Paliat Village can support learning tahfidz Koran because it makes it easier for teachers and students to teach and learn, and improves the quality of reading and memorizing the Koran, can make it easier for children to read the Koran well and correctly in accordance with applicable rules, making students fluent in reading the Koran and avoiding mistakes in the meaning of the Koran